The quality of experience–oriented personal message acquisition optimization for intelligent apparatus in space information networks. (May 2018) - Yao, Changhua; Zhu, Lei
In this article, we investigate the problem of personal message acquisition optimization for intelligent apparatus in the space information network. The quality of experience for persons during achieving the synthetical message rapidly and exactly through the apparatus is significant to the apparatus layout. In this article, we presented a quality of experience–oriented synthetical statistical analysis optimization approach for the personal message acquisition for intelligent apparatus. The main contribution is that the mathematical analysis is combined with the statistical data for the assessment of the personal message acquisition to overcome some drawbacks in the existing works. Experiments verified that the presented approach could make the personal message acquisition with much higher quality of experience.